The Non-equidistant Multivariable New Information MGM(1,n) Based on New Information Background Value Constructing - Zheming He; Xiaoyi Che; Qiyun Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Applying the principle in which new information should be used fully and modeling method of grey system for the problem of lower precision as well as lower adaptability in non-equidistant multivariable MGM(1,n)model, a non-equidistant multivariable new information MGM(1,n) model was put forward which was taken the mth component as the initialization. As the background value is an important factor affecting the precision of grey system model, based on index characteristic of grey model, the characteristic of integral and new information principle, the new information background value in non-equidistant multivariable new information MGM(1,n) was researched and the discrete function with non-homogeneous exponential law was used to fit the accumulated sequence and the formula of new information background value was given. This new non-equidistant multivariable MGM(1,n) model can be used in equidistance & non-equidistance modeling and has the characteristic of high precision as well as high adaptability. Examples validate the practicability and reliability of the proposed model. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.4822